Energy Politics in The Cases of Azerbaijan and Indonesia - Tamami, Kholidah (Syntax Literate, 2021)
Indonesia is the developed countries that have embarked on projects and energy strategies to increase renewables energy since it largely addressed political, economic and environmental goals in their energy security policies. Indonesia concern in energy sector with three parameuteurs, called Promotion and Protection of Investments. The OIC and NAM are the organizations that Azerbaijan and Indonesia are involved in. One of the problems discussed there in is the energy sector. Currently Indonesia and Azerbaijan tried to reduce energy dependence and to achieve environmental sustainability. Policy makers need to pursue a strategy of informing the public with sound evidence while being open about energy policy in general. Indonesia and Azerbaijan have five bilateral agreements. First, opening of RI-Azerbaijan Diplomatic Relations. Second, Cooperation and Consultation between Foreign Ministries. Third, cooperation between News Agencies. Fourth, Visa Exemption for Diplomatic and Service Passport Holders. Fifth, Economic and Technical Cooperation (KSET). The trade balance between both countries is still dominated by the oil and gas sector, and it is not yet reflect the real potential they have, either because trade has so far been through a third country due to the absence of direct sea/air routes, or the lack of market penetration by the Indonesian manufacturing industry. The potential for cooperation that can be worked on between Indonesia and Azerbaijan is in the oil and gas sector given that Azerbaijan is rich in both natural resources. Currently both countries are consolidating the finalization of the P4M to encourage bilateral cooperation in the energy sector, especially oil and gas based. The best collaboration model is to ensure government-to-government long term purchase/contract. One type of descriptive qualitative research is research in the form of a case study method or approach. Case studies are included in the descriptive analysis research, namely research carried out focused on a particular case to be observed and analyzed carefully to completion. A qualitative approach is a process of research and understanding based on methodologies that investigate social phenomena and human problems. alliance theory which was initiated by Kenneth Waltz and international cooperation theory considering that Azerbaijan and Indonesia are members of the OIC and members of NAM countries. An alliance is a formal relationship between two or more groups to achieve a mutually agreed goal or fulfill certain critical business needs of each organization independently.